2015
DOI: 10.1101/lm.038026.114
|View full text |Cite
|
Sign up to set email alerts
|

Principles of designing interpretable optogenetic behavior experiments

Abstract: Over the last decade, there has been much excitement about the use of optogenetic tools to test whether specific cells, regions, and projection pathways are necessary or sufficient for initiating, sustaining, or altering behavior. However, the use of such tools can result in side effects that can complicate experimental design or interpretation. The presence of optogenetic proteins in cells, the effects of heat and light, and the activity of specific ions conducted by optogenetic proteins can result in cellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
104
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(108 citation statements)
references
References 123 publications
(136 reference statements)
3
104
0
1
Order By: Relevance
“…Only red light caused virtually negligible heating for common optogenetic illumination intensities. The development of red sensitive opsins [20][21][22] will therefore lessen the risk of thermal damage in addition to provide better depth penetration.…”
Section: Discussionmentioning
confidence: 99%
“…Only red light caused virtually negligible heating for common optogenetic illumination intensities. The development of red sensitive opsins [20][21][22] will therefore lessen the risk of thermal damage in addition to provide better depth penetration.…”
Section: Discussionmentioning
confidence: 99%
“…First, one must estimate the irradiance threshold at which a neuron can be stimulated or silenced, which is a function of the opsin type, the consistency of expression in a cell, and local neuron orientation 9,169 . A second assumption must be made about the maximum irradiance allowed in tissue before heating 170 and cellular 155 changes occur. A Matlab tool for predicting the tissue irradiance and the heat generated using different spatial and temporal light input was provided by Stujenske et al 170 .…”
Section: Mems Optical Waveguide Integrated Probesmentioning
confidence: 99%
“…A major trend in optogenetic stimulation is the improvement of spatial selectivity because illuminating large volumes of tissue introduces a number of potential confounds to the experiment. There is the possibility of altering the threshold of excitation or creating action potentials because of light absorption and heat 155 and the superposition of multiple spike waveforms on recording channels 156 . Furthermore, stimulating many neurons in synchrony is not a natural way to generate synthetic input 157 ; therefore, we discuss several technological approaches that can address these limitations.…”
Section: Stimulating Brain Activity Introduction To Optogeneticsmentioning
confidence: 99%
“…However, the long-term effects of ChR2 expression is a concern, as Miyashita et al [174] recently demonstrated that high-level, long-term expression of ChR2-EYFP can induce abnormal axonal morphology and affect the organization of cortical circuits. Some opsin expressions can cause toxicity such as aggregation (please see detailed reviews [131,175]). Another issue is that the viral genome is limited in size, especially in adenoassociated virus (AAV); thus, some of the larger promoters such as the inhibitory paralbumin promoter cannot be used in a viral vector.…”
Section: Translational Potential Of Optogenetics and Limitationsmentioning
confidence: 99%